A patient with a 30-year-old Björk-Shiley mechanical mitral valve without anticoagulation for 10 years - Cemal Duzgun, Ali; İlkeli, Ekin (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Today, a wide variety of mechanical mitral valves are implanted for mitral valve pathologies to replace native valves with cardiopulmonary bypass. Life-long use of anticoagulants is essential in mechanical valve patients. Otherwise, serious valve thrombosis leads to fatal outcomes. However, the risk of degeneration of mechanical valves is much lower compared to bioprosthetic valves [1]. We present the case of a 50-year-old female patient with a functional Björk-Shiley mechanical mitral valve who was not using anticoagulation for more than 10 years.